Feeding children with autism in South Africa: the teachers’ perspectives - Adams, Skye N.; Matsimela, Nthabiseng (AOSIS Publishing, 2024)
Background: Over 80% of children diagnosed with autism spectrum disorders (autism) exhibit disruptive behaviours during mealtimes, highlighting the need for personalised care. In South Africa, teachers often take on the responsibility of feeding due to resource constraints and the time children spend at school. Moreover, children with autism have unique and individualised feeding requirements, which many teachers may not have the necessary training or skills to address adequately. Objectives: To explore the ways in which teachers of autistic children manage feeding difficulties in the classroom. Method: A qualitative research design was employed using semi-structured interviews. Eight teachers were interviewed on feeding autistic children between the ages of 3 years - 9 years in Johannesburg, South Africa. Data were transcribed and analysed using thematic analysis. Results: The findings revealed that teachers encountered distinct challenges when it came to feeding autistic children in the classroom, particularly concerning the management of associated feeding difficulties. Teachers employed several strategies to encourage eating in the classroom setting including: (1) bolus modification, (2) behaviour modelling, (3) positive reinforcement and (4) offering choices and alternatives. Conclusion: The study concludes the need for specialised support and training for teachers to address the individualised feeding needs of children with autism. Implementing targeted interventions and providing resources for teachers could enhance their abilities to effectively support children with autism during mealtimes and promote a more inclusive classroom environment. Contribution: This study highlighted the importance of including the teacher in the multidisciplinary team when managing the feeding challenges in children with autism.
Keywords: Autism; Classroom; Feeding support; Teachers; South Africa; SDG-3: Good health and well-being